2012
DOI: 10.1089/jwh.2011.3356
|View full text |Cite
|
Sign up to set email alerts
|

Lower Use of Sexual and Reproductive Health Services Among Women with Frequent Religious Participation, Regardless of Sexual Experience

Abstract: Increasing frequency of current religious service participation was negatively associated with SRH service use among young women, despite sexual experience. Religiously and sexually active young women in the United States may have an unmet need for SRH care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
0
14
1
1
Order By: Relevance
“…Our finding that young women who adhered more closely to their religion’s sexual teachings were more likely to be vaccinated contradicts past research on vaccine intentions (Manhart et al, 2011) and prior findings that more religious young women were less likely to use sexual and reproductive health services (Hall et al, 2012). It is possible that young women in the current study received vaccination as part of primary preventive care and/or through student health, rather than through sexual or reproductive health services.…”
Section: Conclusion and Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our finding that young women who adhered more closely to their religion’s sexual teachings were more likely to be vaccinated contradicts past research on vaccine intentions (Manhart et al, 2011) and prior findings that more religious young women were less likely to use sexual and reproductive health services (Hall et al, 2012). It is possible that young women in the current study received vaccination as part of primary preventive care and/or through student health, rather than through sexual or reproductive health services.…”
Section: Conclusion and Discussioncontrasting
confidence: 99%
“…Similarly, parents who attend religious services less frequently have greater intentions to get their children vaccinated than more religious parents (Barnack, Reddy, & Swain, 2010). In addition, young women who attend religious services more frequently are less likely to use sexual and reproductive health services (Hall, Moreau, & Trussell, 2012). However, religiosity is multifaceted, encompassing both public components, such as religious behavior, and private components, such as religious attitudes (King & Boyatzis, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, our study did not include a robust set of religiosity or perceived norm measures, nor did it include items to assess women's self-described reasons, including the role of religion, for disagreement. Given that the links between political affiliation, religiosity, and women's acceptability of the ACA are likely complex, interrelated with other microand macro-level factors, including sociopolitical and cultural norms, and have potentially important implications for women's health service use, 9,10,34,35 additional research focused on disentangling these relationships is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies were conducted among African populations and while some showed that religious affiliation was associated with an increased risk of HIV and a lower uptake of HIV testing (Addis et al, 2013;Hawkes et al, 2013;Mohamed & Mahfouz, 2013), others concluded that strong religious beliefs were unlikely to act as a barrier to accessing HIV testing (Fakoya et al, 2012). More broadly, religiosity has been reported to be negatively associated with use of sexual and reproductive health services (Hall, Moreau, & Trussell, 2012) and with lack of disclosure (Préau, Bouhnik, Roussiau, Lert, & Spire, 2008). LP or PAD was particularly high among SSA migrants.…”
Section: Aids Care S89mentioning
confidence: 99%